Sample pretreatment for the capillary electrophoretic determination of organic acids in chromium(III) plating baths. Issue 24 (16th November 2015) - Taraba, Lukáš; Křížek, Tomáš; Kubíčková, Anna; Coufal, Pavel
Abstract : This work deals with the development and optimization of the sample pretreatment and consequent electrophoretic analysis of two modern plating baths containing chromium(III) and either citric acid or oxalic acid. Some model mixtures containing known amounts of components of industrial baths have been prepared to simulate simplified bath matrices. Prior to analysis, a sample pretreatment consisting of the addition of some agents that could release acid from the stable chromium complex was tested. Determination of organic anions was accomplished by indirect UV detection. The best results were achieved by precipitation of chromium(III) hydroxide. The content of oxalate and citrate in real samples was calculated as 96.5% (SD 2.3%) and 97.3% (SD 0.8%), respectively, of the declared amount. Very good robustness of the method and satisfactory repeatability of migration time and peak area were obtained. This simple inexpensive method is suitable for routine determination of citric and oxalic acid in chromium(III)‐based plating baths.